Reaksi Detak Jantung Musisi Amatir dan Non-Amatir Terhadap Repatoar Klasik Bertempo Cepat dan Lambat dan Musik Dangdut. - Giovanli Lauren; Tommy Pik (Jurusan Seni dan Desain, Fakultas Sastra, Universitas Negeri Malang, 2019)
The importance of music in our daily life has given rise to an increased number of studies addressing the brain regions involved in its appreciation. Some of these studies controlled only for the familiarity of the stimuli, while others relied on pleasantness ratings, and others still on musical preferences. With a listening test and a recorded heart rate ratings experiment, we wished to clarify the role of familiarity in the brain correlates and the reaction of cardiovascular system of music appreciation by controlling, in the same study, for both familiarity and musical preferences. First, we conducted a listening test, in which participants rated the familiarity and liking of song excerpts from the classical repertoire and dangdut. Music the recorded fluctuation of heart rate gives us a slight information that there is/are factors that influence human biology system to respond music, aside from the natural respond of body to music in terms of experience that amateur and non-amateur musician had. Hence, familiarity seems to be a crucial factor in making the listeners emotionally engaged with music.